Cytological Pattern of Bronchial Carcinoma in Male Patients Seen in Tertiary Care Hospital - Basak, PM; Khan, MMR; Sarker, BC; Saha, CK; Pal, BK; Islam, N; Devi, R; Das, HS; Khanam, K (TAJ: Journal of Teachers Association, 2018)
This cross sectional descriptive study was conducted to assess cytological characteristics of bronchial carcinoma in 60 patients from various region of Rajshahi Division presenting with clinical features consisting with the diagnosis of lung carcinoma. They were admitted to Rajshahi Medical College Hospital from January 2013 to December 2013. Our observations reveals that the most prevalent malignancy among these patients was non small cell lung carcinoma including squamous cell carcinoma and large cell carcinoma in males patients. The common site of bronchial carcinoma in the upper lobe of lung. The proper treatment of bronchial carcinoma depends on the cytological pattern of bronchial carcinoma. TAJ 2013; 26: 27-29